A house out of town... (XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2018)
Admitting that I’ve never been in the spaces of neighbouring planets, I’m looking for an approach to the theme very personal here, and somehow similar to that of classical science fiction (‘50s–’70s of last century); a world in which the first investigation, starting from the possible future inventions, was in reality oriented towards possible human behaviours and the action of human beings in the face of new situations. We can thus see that, if there was a lot of thought in that direction, few images could then represent the built space, which is more interesting here. We already have problems, with the habit of politically correctness, if only try to represent human beings, who all want to emerge in the media, in their different forms, genres, colours, ethnicity... Perhaps, however, we can imagine something of the spaces, but only starting from large categories, with simple shapes, with great simple solutions. The structure of the soap bubbles is the structure that teaches the most. Caves have been one of the safest shelters for millennia. The past has made us glimpse so much: monsters, spaceships, possible worlds, strange aliens; but very little on the shape of the possible built spaces. That is a theme inherent in contemporary “narration”, where we hope that the solution to human problems lay not in their wisdom (perhaps no one believes it) but in the superheroes, which are now considered by the media as the true actors of human fortunes. It is also interesting to note that in more remote times, those of J. Verne, the illustrations followed the story carefully; while in more recent times we have been limited especially to the covers, which were however a form of precise reference, suggestion, but not a real description of the situation. The world of comics is different, and I’ll leave it aside: it deliberately keeps itself away from reality, in an apparently parallel way, not “con–” or “di–verging”, often going towards superheroes or something similar; but this world has shown itself in time, instead, in some way, capable of influencing not so much the construction as the appearance of individuals, the fashion itself. Some mention is made on the forms that those built spaces may have, remembering how these same spaces are already evolving today on earth, but especially remembering that these spaces will have to be completely different from each other, on other planets; different between planet and planet, depending on the different value of gravity force and therefore the different possibilities of the simplest human behaviour. And to stay on the personal approach, even some original illustration.